Safeguarding Maritime Operations through Strategic Shipping Protocols for Enhanced Security: Melindungi Operasi Maritim melalui Protokol Pelayaran Strategis untuk Meningkatkan Keamanan - Alfariqi, Amar; Akbar, Ali (Procedia of Engineering and Life Science, 2024)
This study investigates the implementation of safety measures during the shipping of survey boats in Indonesia, employing qualitative methods with both primary and secondary data. Maritime transport safety, particularly for survey boats, is crucial yet often overlooked. The analysis reveals that effective management of survey boats and fuel safety is essential, with specific measures such as careful navigation, no-smoking policies, secure fuel packaging, regular maintenance, and weather monitoring being paramount. The findings advocate for stringent safety protocols to prevent accidents and enhance maritime security, suggesting significant implications for global maritime operations. Highlights: Importance of Shipping Safety: Priority in sea transportation. Analysis of Shipping Safety Implementation: Focus on survey boat usage and fuel safety. Key Variables in Research: Safe driving practices, fuel packaging, ship maintenance, weather awareness. Keywords: Surveyboat, Fuel, Safety